1998
DOI: 10.1007/s003300050540
|View full text |Cite
|
Sign up to set email alerts
|

Power Doppler sonography: general principles, clinical applications, and future prospects

Abstract: Power Doppler sonography (PD) is a technique that displays the strength of the Doppler signal, rather than the flow velocity and directional information. Its increased flow sensitivity and better vascular delineation have been used to document the presence and characteristics of flow in vessels that are poorly imaged with conventional color Doppler (CD), to identify areas of ischemia, to demonstrate inflammatory hyperemia or increased and irregular flow in tumors, as well as to assess serial vascular changes r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
50
1
13

Year Published

2001
2001
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 57 publications
1
50
1
13
Order By: Relevance
“…Recently, high resolution pulsed and color Doppler US (CD) are widely used as noninvasive procedures that can easily obtain interesting data about the vascularity of parenchymatous structures. Recent investigators have indicated that the contemporary means of evaluating morphology and vascular structures may have an important role in the differential diagnosis of benign and malignant tumor [8][9][10][11][12][13][14]. But, to date, the application of power Doppler US to thyroid follicular tumor analysis has not been demonstrated as having definite clinical usefulness.…”
mentioning
confidence: 99%
“…Recently, high resolution pulsed and color Doppler US (CD) are widely used as noninvasive procedures that can easily obtain interesting data about the vascularity of parenchymatous structures. Recent investigators have indicated that the contemporary means of evaluating morphology and vascular structures may have an important role in the differential diagnosis of benign and malignant tumor [8][9][10][11][12][13][14]. But, to date, the application of power Doppler US to thyroid follicular tumor analysis has not been demonstrated as having definite clinical usefulness.…”
mentioning
confidence: 99%
“…This has further expanded the usefulness of color Doppler ultrasonography as a tool for reproductive research. Power Doppler's independence from probe angle restriction has proven to make it more sensitive and accurate when measuring and quantifying the blood flow of small or irregular tissues, vessels and organs (Martinoli et al, 1998b;Ginther, 2007;.…”
Section: Ultrasonographymentioning
confidence: 99%
“…Luteal dysfunction can cause irregular estrous cycles and embryonic mortality which lead to decreased pregnancy rates . Power Doppler ultrasonography allows the quantification of blood perfusion of small and irregular tissues, such as the CL (Martinoli et al, 1998). determined that power Doppler was a reliable, accurate, and repeatable method of quantifying luteal blood perfusion.…”
Section: Introductionmentioning
confidence: 96%
“…Rheumatoid synovium is imaged by using color Doppler or power Doppler modes. The latter is thought to be better suited for depicting slow flows 3 , although there is an article in the literature showing no big difference between these modes 4 .…”
Section: To the Editormentioning
confidence: 99%